Effect of the Elaboration Method on Structural and Optical Properties of Zn1.33Ga1.335Sn0.33O4:0.5%Cr3+ Persistent Luminescent Nanomaterials - Guanyu Cai; Luidgi Giordano; Cyrille Richard; Bruno Viana (Nanomaterials, 2023)
Near-infrared (NIR) persistent luminescence (PersL) materials have demonstrated promising developments for applications in many advanced fields due to their unique optical properties. Both high-temperature solid-state (SS) or hydrothermal (HT) methods can successfully be used to prepare PersL materials. In this work, Zn1.33Ga1.34Sn0.33O4:0.5%Cr3+ (ZGSO:0.5%Cr3+), a newly proposed nanomaterial for bioimaging, was prepared using SS and HT methods. The results show the crystal structure, morphology and optical properties of the samples that were prepared using both methods. Briefly, the crystallite size of the ZGSO:0.5%Cr3+ prepared using the SS method is ~3 µm, and as expected, is larger than materials prepared using the HT method. However, the growth process used in the hydrothermal environment promotes the formation of ZGSO:0.5%Cr3+ with more uniform shapes and smaller sizes (less than 500 nm). Different diameter ranges of nanoparticles were obtained using HT and ball milling (BM) methods (ranging from 25–50 nm) and by using SS and BM methods (25–200 nm) as well. In addition, the SS-prepared microstructure material has stronger PersL than HT-prepared particles before they go through ball milling to create nanomaterials. On the contrary, after BM treatment, ZGSO:0.5%Cr3+ HT and BM NPs present higher PersL and photoluminescence (PL) properties than ZGSO:0.5%Cr3+ SS and BM NPs, even though both kinds of NPs present worse PersL and PL compared to the original particles before BM. To summarize: preparation methods, whether by SS or HT, with additional grinding as a second step, can have a significant impact on the morphological and luminescent features of ZGSO:0.5%Cr3+ PersL materials.